2000
DOI: 10.1177/026553220001700203
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of a foreign language at the end of primary (elementary) education

Abstract: The National Assessment Programme in Education (PPON) measures the level of performance on school subjects at the end of Dutch primary (elementary) education. Two assessments, in 1991 and 1996, of English as a foreign language have been conducted. This article reports on the outcomes of both assessments with regard to listening, reading and word knowledge. There is a slight decrease in pupils’ performances when the outcomes of the 1996 assessment are compared to the 1991 assessment. Large differences in perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…From a summative perspective, early YL assessment studies used data obtained in the context of national assessments that were administered at the end of primary education in various countries (e.g., Edelenbos & Vinjé, 2000; Johnstone, 2000; Zangl, 2000). For example, Edelenbos and Vinjé (2000) analyzed data collected in a National Assessment Programme in Education that aimed at measuring YLs’ achievements in English as a foreign language (EFL) at the end of their primary education in the Netherlands. Assessments were administered in paper-and-pencil format (listening, reading, receptive word knowledge, use of a bilingual wordlist) and in individual face-to-face sessions with an interlocutor.…”
Section: The Larger Picture: What Is the Construct And How Has It Chamentioning
confidence: 99%
See 3 more Smart Citations
“…From a summative perspective, early YL assessment studies used data obtained in the context of national assessments that were administered at the end of primary education in various countries (e.g., Edelenbos & Vinjé, 2000; Johnstone, 2000; Zangl, 2000). For example, Edelenbos and Vinjé (2000) analyzed data collected in a National Assessment Programme in Education that aimed at measuring YLs’ achievements in English as a foreign language (EFL) at the end of their primary education in the Netherlands. Assessments were administered in paper-and-pencil format (listening, reading, receptive word knowledge, use of a bilingual wordlist) and in individual face-to-face sessions with an interlocutor.…”
Section: The Larger Picture: What Is the Construct And How Has It Chamentioning
confidence: 99%
“…The latter included a focus on speaking elicited through a discussion with English-speaking partners, pronunciation gauged by means of reading aloud sentences, and productive word knowledge tested by providing students with pictures that they had to label or describe. Edelenbos and Vinjé (2000) found that overall students performed well in listening, but not in reading. In particular for reading, they noted better outcomes if teachers used a communicative approach instead of a grammar-oriented one, while the latter approach tended to result in higher scores in word knowledge.…”
Section: The Larger Picture: What Is the Construct And How Has It Chamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Edelenbos and Vinje (2000) have monitored the English performance levels of Dutch primary school children; two of the variables analysed were time spent on learning English and their teachers' pedagogical orientation. A programme of ongoing classroom research, and a content analysis derived from extended observations of primary foreign language classrooms (e.g.…”
mentioning
confidence: 99%